Prilog historiji dubrovačkog antuninskog roda Kladorubovići (Povijesni prilozi (Historical Contributions), 2019)
Ragusan society represents an open and rewarding research topic as well as a space for the creative engagement of researchers from various professions. An important basis for its evaluation is Vlajki’s genealogy of Antunines (VGA), a kind of a “memory book” of this social layer, shaped according to the needs of constructing the markers of their identity (Zrinka Pešorda Vardić). The VGA is not a chronicle based on primary sources but is also a partial recapitulation of the oral tradition that was shaped in line with contemporary requirements and deliberate interventions from later times. The earliest information about certain families in the VGA should be subjected to additional enquiry, and this paper treats one such case on the example of the Kladorubović kindred. Namely, contrary to the claims of the VGA, the founder of the family MirkoPribinjić, also known asKladorup, was not a member of the nobility, his arrival to Ragusa is not connected to the murder committed on the Bosnian royal court, and he did not come from Srebrenica but rather from Cernica. The individual who shaped these claims about the Kladorubovići in the VGA unjustifiably favoured Srebrenica over Cernica. The presented sources show that the reconstruction of the Kladorubović family tree is an open task. Further research of archival sources regarding the descendants of Radonja and Stjepko Mirković will enable the creation of a more complete image of the family. Through archival documents we have gathered information about the cousin of Marko Pribinjić, his son Stjepko Mirković as well as his descendants and daughter Dominika, all of who are absent from the VGA. Even though they are mentioned in passing, these documents uncover the business arrangements, dwelling places, connections to others, and the rise of the family on the social ladder. The gathered sources allow for a monograph study to be composed about the Kladorubovići. The material allows for an assumption that certain problems among the descendants of the two brothers, Stjepko and Radonja Mirković, arose from the testament of their father Mirko Pribinjić Kladorub. It is also supposed that problems within the family are the reason why the information about its members in the VGA are shaped in such a way, why certain information is clearly lacking, as the family story was shaped by the members of the stronger and more influential line of Radonja Mirković and not by unbiased and independent researchers of historical sources.